Elemental Analysis of Some Important Tobacco Varieties (Nicotiana tabacum L.) by WDXRF Spectroscopy - CAMAS, NECDET; KARABULUT, BUNYAMIN; KARABULUT, ABDULHALIK (Asian Journal of Chemistry, 2010)
Wavelength dispersive X-ray fluorescence (WDXRF) analysis, a rapid and non-destructive technique, is used for determining trace and heavy elements in tobacco selected from different districts of Turkey. By this technique, 22 non-organic elements are determined. The concentrations of substance are given both as per cent type of dry weight and as part per million (ppm). The variations of heavy metal and trace element concentrations in tobacco leave show small change depending on the region where the leaves are harvested. The accuracy of the measurements is evaluated to 4th order of magnitude and the results are compared with the standards CTA-OTL-1 (Oriental) and CTA-OTL-2 (Virginia) tobacco leaves.